Estimates of Maternal Mortality Ratio and the associated medical causes in Orissa and Rajasthan States - A cross sectional study - Aggarwal, Abha Rani; Kar, Ranjana; Pandey, Arvind (Indian Journal of Community Health, 2015)
Background: Maternal Mortality Ratio (MMR) is an important indicator of reproductive health and its reduction remains a challenge in India. Aims &Objective: This study was conducted with the aim of estimating MMR in two states Orissa and Rajasthan having high MMR as well as to identify the associated medical causes of maternal mortality. Material Methods: This survey was conducted from October 2010-June 2012 on a sample of 13 Primary Health Centres (PHCs) in Orissa and 15 PHCs in Rajasthan. These numbers have been derived after estimating the total number of live births using MMR and birth rate from Sample Registration System. 1997-2003.An adapted snowball technique was adopted wherein maternal deaths were captured by snowball technique and the numbers of live births were taken from the available records from the various health facilities in the study. Results: The overall birth rate in Orissa was found to be 19 per 1000 population while in Rajasthan it was 24 per 1000 population. The study revealed that 17% additional maternal deaths could be captured by snowball technique as against the official record. The overall weighted estimate of MMR was 252 per one lakh live births (95% CI: 246-259 per 1,00,000 live births) in Orissa and 209 per one lakh live births (95% CI: 207-211 per one lakh live births) in Rajasthan. The main causes of maternal deaths were post-partum haemorrhage, anaemia and septicaemia. More than 25% maternal deaths could be attributed to indirect causes including suicide, accident and infectious diseases. Conclusion: There appears to be a positive trend towards reduction of maternal mortality in Orissa and Rajasthan. Greater care is essential to reduce medical as well as incidental causes of death during pregnancy.